2009
DOI: 10.1007/s00382-009-0554-3
|View full text |Cite
|
Sign up to set email alerts
|

Storm track sensitivity to sea surface temperature resolution in a regional atmosphere model

Abstract: A high resolution regional atmosphere model is used to investigate the sensitivity of the North Atlantic storm track to the spatial and temporal resolution of the sea surface temperature (SST) data used as a lower boundary condition. The model is run over an unusually large domain covering all of the North Atlantic and Europe, and is shown to produce a very good simulation of the observed storm track structure. The model is forced at the lateral boundaries with 15-20 years of data from the ERA-40 reanalysis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 32 publications
5
57
0
Order By: Relevance
“…Classical studies showed that these quasi-stationary waves were maintained by a combination of topographic and thermal forcing; see Held (1983, and references therein). Several recent studies (Brayshaw et al 2008;Nakamura et al 2008;Woollings et al 2010b;Liu et al 2013) have also considered the influence of a large-scale SST front on the tilted storm track across the NAB. These planetaryand basin-scale pictures emphasize the remote influence of zonal asymmetries in Northern Hemisphere topography and thermal forcing-like the Rockies, Himalayas, and land-ocean contrasts-or that of large-scale fronts, while our rectilinear, tilted-jet model highlights the potential role of regional, fairly small-scale thermal and mechanical driving by an SST front.…”
Section: B Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Classical studies showed that these quasi-stationary waves were maintained by a combination of topographic and thermal forcing; see Held (1983, and references therein). Several recent studies (Brayshaw et al 2008;Nakamura et al 2008;Woollings et al 2010b;Liu et al 2013) have also considered the influence of a large-scale SST front on the tilted storm track across the NAB. These planetaryand basin-scale pictures emphasize the remote influence of zonal asymmetries in Northern Hemisphere topography and thermal forcing-like the Rockies, Himalayas, and land-ocean contrasts-or that of large-scale fronts, while our rectilinear, tilted-jet model highlights the potential role of regional, fairly small-scale thermal and mechanical driving by an SST front.…”
Section: B Discussionmentioning
confidence: 99%
“…Luo et al (2012) recently summarized studies of NAO subannual variability. Woollings et al (2010a) showed that a good characterization of the changes in both strength and latitude of the jet stream's eddy-driven component requires the phase of the east Atlantic (EA) pattern in addition to the NAO; this pattern (Wallace and Gutzler 1981) consists of a pressure monopole over the North Atlantic with a center that lies between the two centers of the NAO dipole.…”
Section: Introductionmentioning
confidence: 99%
“…Minobe et al (2008; and Taguchi et al (2009) have recently discovered a close relationship between eddy activity and ocean fronts. Woollings et al (2010) argued that the temporal resolution of prescribed sea surface temperatures is important. Ensemble experiments could be performed with different sea surface temperature distributions as a surface BC for the RAM.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…With the smoothed SST front, the frequency of explosive deepening events increases over the NEP, and this feature is similar to the storm-track response to Kuroshio Extension variability in O' Reilly and Czaja (2015). Conventionally used storm-track indices, such as the EGR, y 0 T 0 , and y 0 y 0 (Nakamura and Yamane 2010; Sampe et al 2010;Woollings et al 2010;Hotta and Nakamura 2011;Ogawa et al 2012;Iizuka et al 2013;Small et al 2014), are also examined. Figure 4a shows the EGR difference at 850 hPa between CNTL and SMTHK in January (EGRC 2 EGRS).…”
Section: Storm-track Responsementioning
confidence: 99%